Significance of Degree of HLA Disparity Using T-cell Replete Peripheral Blood Stem Cells From Haploidentical Donors With Posttransplantation Cyclophosphamide in AML in First Complete Hematologic Remission: A Study of the Acute Leukemia Working Party of the EBMT - Kharfan-Dabaja MA; Labopin M; Ayala E; Bazarbachi A; Blaise D; Vydra J; Bramanti S; Itala-Remes M; Schmid C; Busca A; Forcade E; Rabitsch W; et al. (LIPPINCOTT WILLIAMS & WILKINS, 2025)
Availability of haploidentical donors has broadened utilization of allogeneic hematopoietic cell transplantation (allo-HCT). Peripheral blood stem cells (PBSC) are being used with increased frequency in haploidentical allo-HCT. We evaluated extent of HLA disparity (2-3/8 versus 4/8 HLA antigen mismatches) on post-allograft outcomes when using T-cell replete PBSC from haploidentical donors for acute myeloid leukemia in first complete remission. Primary objectives entailed assessing cumulative incidence of grade 2-4 acute graft -versus-host disease (GVHD) and chronic GVHD (any grade). A total of 645 patients received a haploidentical allo-HCT from a donor with either 2-3 of 8 HLA antigen mismatches (n = 180) or with 4 of 8 HLA antigen mismatches (n = 465). Presence of 2-3 of 8 versus 4 of 8 HLA mismatches did not affect the incidence of acute GVHD (grade 2-4) and chronic GVHD (any grade). Overall survival (OS), leukemia-free survival (LFS) relapse incidence (RI), nonrelapse mortality and the composite endpoint of GVHD-free relapse-free survival were also similar among the groups. Pertaining to HLA-B leader matching effect, our analysis did not discern any difference in aforementioned post-allograft outcomes for this variable. However, in univariate analysis, absence of an antigen mismatch in HLA-DPB1 showed a trend for better OS. Notwithstanding inherent limitations associated with registry data, our results did not show an advantage of selecting a haploidentical donor with 2-3 of 8 HLA antigen mismatches over one with 4 of 8 HLA antigen mismatches when using PBSC as the cell source. Adverse cytogenetics remains a major adverse determinant of inferior OS and LFS and a higher RI. Using reduced-intensity conditioning yielded worse OS and LFS.